Elucidating the tunability of binding behavior for the MERS-CoV macro domain with NAD metabolites - Meng-Hsuan Lin (Nature Portfolio, 2021)
Meng-Hsuan Lin et al. investigate MERS-CoV macro domain binding selectivity with NAD and NAD metabolites under various conditions. At physiological temperature, NAD is observed to have enhanced binding affinity to the MERS-CoV macro domain, shedding light on a new possible role of the MERS-CoV macro domain in viral replication.